2021
DOI: 10.3390/jcm11010096
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Assessment of Monocyte HLA-DR Expression and Ex Vivo TNF-α Release as Markers of Adverse Outcome after Various Injuries—Insights from the REALISM Study

Abstract: Intensive care unit (ICU) patients develop an altered host immune response after severe injuries. This response may evolve towards a state of persistent immunosuppression that is associated with adverse clinical outcomes. The expression of human leukocyte antigen DR on circulating monocytes (mHLA-DR) and ex vivo release of tumor necrosis factor α (TNF-α) by lipopolysaccharide-stimulated whole blood are two related biomarkers offered to characterize this phenomenon. The purpose of this study was to concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Pros and cons of mHLA-DR expression, TNF-α secretion, and ALC as prognostic indicators in sepsis IP are summarized in Table 2 ( 4 , 26 , 27 , 30 , 35 , 130 , 138 , 139 ). mHLA-DR expression and TNF-α responsiveness seek to measure similar biology of innate immune MNP dysfunction ( 26 , 27 , 130 ).…”
Section: Comparison Of Hla-dr Tnf-α Secretion and Alcmentioning
confidence: 99%
See 1 more Smart Citation
“…Pros and cons of mHLA-DR expression, TNF-α secretion, and ALC as prognostic indicators in sepsis IP are summarized in Table 2 ( 4 , 26 , 27 , 30 , 35 , 130 , 138 , 139 ). mHLA-DR expression and TNF-α responsiveness seek to measure similar biology of innate immune MNP dysfunction ( 26 , 27 , 130 ).…”
Section: Comparison Of Hla-dr Tnf-α Secretion and Alcmentioning
confidence: 99%
“…Nonetheless, testing for this biomarker requires flow cytometry of fresh or stabilized cells, necessitating either shipping to a central facility or timely local analysis ( 74 , 140 ). By contrast, TNF-α secretion requires local site addition of LPS to blood samples and incubation followed by analysis of frozen cell supernatants by enzyme-linked immunosorbent assay (ELISA) ( 138 ). This procedure generates need for trained site staff to perform ex-vivo LPS stimulation reliably.…”
Section: Comparison Of Hla-dr Tnf-α Secretion and Alcmentioning
confidence: 99%
“…Elevated levels of these suppressor cells have frequently been reported in sepsis patients, re ecting severity of disease and predisposition to secondary infections, but very seldomly in injury, such as in our study, prior to the occurrence of a primary infection [50][51][52]. The second recent large multicenter study explored mHLA-DR and ex vivo TNF-α release in sepsis, trauma and postoperative patients in association with adverse clinical outcome (death or secondary infection) [19,28]. It showed persistent decreases of both markers at days 5-7 post ICU admission to be associated with both outcomes, whatever the type of injury.…”
Section: Discussionmentioning
confidence: 65%
“…The most commonly studied parameter of immune dysfunction associated with injury is the low HLA-DR expression on monocytes (mHLA-DR), which induces an impaired functional state of these cells. The latter feature has been associated with secondary sepsis and sometimes outcome in severe trauma, burn and postoperative patients [15][16][17][18][19][20][21].Targeted treatment has been tempted in that context. Older studies have shown contrasted clinical outcomes after immunotherapy, based on GM-CSF or IFNγ administration, despite e cacious restoration of mHLA-DR and/or IFNγ endogenous secretion [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation